Modernizing of Plant Records Management: A Case Study of UUM’S Herbs Garden - Mohd Nawi, Nur Syazwani; Mat Yamin, Fadhilah; Wan Ishak, Wan Hussain; Abdul Wahab, Siti Nur Aziah; Abdul Hamid, Fatin Liyana (2023)
Innovation supported in the application of information and communication technology (ICT) triggered the start of the digital economy and opened many opportunities and organizational efficiencies. Likewise, in the management of trees or plants, the need to manage information, data and records in a systematic, efficient and effective manner needs to be emphasized. The plant's manual record-keeping system is not relevant anymore in this new digital era and requires a more proficient solution. Therefore, this study focuses on developing a Herb Garden Management System (HGMS) to improve the efficiency of herb garden management at Universiti Utara Malaysia (UUM). Information systems that were previously used manually will be converted into digital form to facilitate data storage and avoid duplication of information. The respondent is the workers from the Agricultural, Landscape, Forestry Units, Department of Development and Maintenance (JPP), UUM. They are the responsible unit that maintains and care for UUM’s landscape and environment, including the herb garden. This study was conducted through observation and face-to-face interview. By implementing a centralized database significantly enhances data accessibility and control. In conclusion, this study emphasizes the importance of good plant management in forming a sustainable landscape to conserve natural resources, especially in university green areas.